2001
DOI: 10.1146/annurev.nutr.21.1.23
|View full text |Cite
|
Sign up to set email alerts
|

FAT METABOLISM IN INSECTS

Abstract: The study of fat metabolism in insects has received considerable attention over the years. Although by no means complete, there is a growing body of information about dietary lipid requirements, and the absolute requirement for sterol is of particular note. In this review we (a) summarize the state of understanding of the dietary requirements for the major lipids and (b) describe in detail the insect lipid transport system. Insects digest and absorb lipids similarly to vertebrates, but with some important diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
399
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(412 citation statements)
references
References 144 publications
9
399
1
3
Order By: Relevance
“…It was possible that the disturbance in fatty and amino acids was a result of TCA cycle disruption. Fatty acids, also as an energy source, are an integral part of cell membranes (Canavoso et al 2001). Cell membrane fluidity, which is dependent on the lipid and fatty acid composition, is vital for normal cell functions (Werner and Simmons 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that the disturbance in fatty and amino acids was a result of TCA cycle disruption. Fatty acids, also as an energy source, are an integral part of cell membranes (Canavoso et al 2001). Cell membrane fluidity, which is dependent on the lipid and fatty acid composition, is vital for normal cell functions (Werner and Simmons 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the main portion of fat body total lipids is triacylglycerides (Canavoso et al 2001), which are part of the neutral or simple lipids. To confirm that this is the case in L. decemlineata the abdominal total lipids were fractioned.…”
Section: Lipid Fractioning Methodsmentioning
confidence: 99%
“…In the fat body, most hemolymph lipids garnered from the breakdown of food are converted into neutral lipids (triglycerides or triacylglycerides) (Arrese & Soulages 2010). Neutral lipids are the main form of storage lipids in the insect fat body, usually constituting more than 90 % of the fat body total lipid mass (Canavoso et al 2001). It is of importance to note that also reproductively active individuals gather lipids, which are used for oogenesis and to fuel mating behavior, and that these lipids also can be in the form of neutral lipids stored in the fat body (de Loof & Lagasse 1970).…”
Section: Latitudinal Patterns In Life-history Traits In Seasonal Envimentioning
confidence: 99%
“…H. subflexa larvae feed exclusively on the fruits of Physalis spp., which are physically encased within an inflated calyx of the flower and defended by the presence of secondary compounds (e.g., withanolides and flavonol glycosides) (12,13). We have discovered an additional feature of these fruits that might be expected to deter insect herbivory: P. angulata fruits lack an important fatty acid, linolenic acid (LA), which is required for the normal development and metamorphosis of most insect larvae (14)(15)(16).…”
mentioning
confidence: 99%